PENGARUH UPAH DAN TEKNOLOGI TERHADAP PRODUKTIVITAS DAN PENYERAPAN TENAGA KERJA PADA INDUSTRI MEBEL DI KOTA DENPASAR - Nurfiat, Nashahta Ardhiaty; Rustariyuni, Surya Dewi (PIRAMIDA; Vol 14 No 1 (2018): PIRAMIDA`- Jurnal Kependudukan dan Pengembangan Sumber Daya Manusia, 2018)
Small industry has a very important role in the Province of Bali, especially in the city of Denpasar in providing employment opportunities for the community. The development of this small industry will reduce unemployment and poverty. The purpose of this study is to analyze 1) The influence of wage and technology level on work productivity 2) Effect of wage rate, technology and work productivity on labor absorption 3) Indirect influence of wage and technology level on labor absorption through work productivity. This research was conducted in Denpasar City with respondents of wooden furniture industry entrepreneurs covering 4 subdistricts namely North Denpasar, East Denpasar, South Denpasar and West Denpasar. Objects in this study include wage rates, technology, work productivity and employment. The sample in this study amounted to 104 respondents. The sample technique used is probability sampling or simple random sampling. Data collection methods used in this study include observation, questionnaires and in-depth interviews. Data analysis technique used is path analysis / path analysis and test of sobel to analyze indirect influence through intervening variable. Based on the research results obtained conclusion that the level of wages and technology postive and significant influence on the productivity of wood furniture industry desk work. Variable wage rate, technology and work productivity have a positive and significant effect to the absorption of labor of wooden table furniture industry in Denpasar City. Work productivity variable is the variable of mediation of indirect influence of variable of wage rate and technology to the absorption of labor in wooden furniture industry in Denpasar City. Suggestion from this research entrepreneurs have the policy of giving the right incentive or bonus to the workforce so as to increase the production.